Penentuan Komoditi Unggulan UKM Kota Batam Menggunakan Analytical Hierarchy Process - Dwi Kartikasari (Politeknik Negeri Batam, 2009)
A research about the development of micro, small and middle scale enterprise (UMKM) in Riau Islands has been conducted by Bank Indonesia and Politeknik Batam. The objectives of this research are (1) to know the application of AHP method for determining primary commodities/products/kinds of UMKM and (2) to give information about of business which needs to be the priority to be developed in Batam according to AHP method. The research was conducted in 11 sub districts in municipality of Batam involving respondents/experts/ stakeholders of the sub district and district. There are four steps ranking in applying AHP method, which is weighting 4 criteria in sub district level, 11 criteria in municipal level, 3 research goals, and 10 sectors level. The result of this research is that snack as part of industrial sector is considered as superior commodity of UKM to develop in Batam.